Switching Intention and Intention to Use Personal Cloud Storage Services Among Chinese Undergraduates - Li, Pan; Varghese, Manoj Mechankara (Scholar: Human Sciences, 2023)
Purpose: As one of the emerging Internet technologies, cloud technology may be broadly categorized as cloud computing and cloud storage. Personal Cloud Storage Service (PCSS) is an important part of cloud technology. Thus, this study investigates the factors influencing Hangzhou undergraduates’ switching intentions and intention to use personal cloud storage services. Research design, data, and methodology: The data were collected from 515 undergraduates at Zhejiang University, Zhejiang Gongshang University, and Zhejiang University of Technology. The sampling techniques are judgmental sampling, stratified random sampling, and snowball sampling. The item-objective congruence (IOC) and Cronbach’s Alpha of the pilot test were approved before the data collection. Afterwards, this study applied confirmatory factor analysis (CFA) and structural equation modeling (SEM). Results: The findings indicate that perceived ease of use has a significant impact on perceived usefulness. Perceived usefulness, perceived ease of use and attitude significantly affect intention to use. Perceived risk significantly affected the switching intention. Finally, switching cost and perceived usefulness significantly affect the switching intention. Conclusion: Personal cloud storage service providers should enhance the security and should continue to improve its PCSS products and optimize the membership price model, enabling free users to use the service by sending them advertisements.